Optimization of The Digital Game Based Learning Instructional Design (DGBL-ID) Method as Learning Support Media - Dani Arifudin; Eka Sulistiyaningsih; Intan Adila Kautsar (Institute of Computer Science (IOCS), 2020)
The development of science and technology has encouraged reforms in the use of technology results in the learning process. As a teacher, you must package learning to be creative, innovative, and fun in order for learning to be successful. One way for learning to package learning to be interesting is to use learning media. One of the learning methods that can be applied to an angragogical approach and is effective in achieving learning objectives is learning using digital game-based learning methods (DGBL). This study aims to develop game-based learning in order to create a learning environment that is motivating, fun, and enhances creativity. Through a game-based learning approach in learning, it is hoped that the DGBL-ID method can stimulate emotional, intellectual, and psychomotor activities through the aspects of interactivity, direct feedback, virtual representations and repetition of settings and events in a lesson.